PENGEMBANGAN MEDIA MANIPULATIF UNTUK MENINGKATKAN PENCAPAIAN PEMBELAJARAN DAN KEMAMPUAN BERPIKIR KRITIS PADA MATERI SISTEM TATA SURYA SISWA KELAS VI - Chotimah, Kusnul (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
The aim of this research is to produce solar system manipulative media that meets the requirements and is effective in learning the solar system. This research uses the development method with the PLOMP model, with research subjects consisting of 22 students in the experimental class and 27 students in the control class. The results of the paired sample t-test were carried out to determine whether there were differences between the pretest and posttest results of students in the experimental class and the control class. The results showed that there was a significant influence before (pretest) and after the use of solar system manipulative media (posttest) on increasing student learning outcomes in science subjects with the material